การชุบสังกะสีแบบจุ่มร้อนโดยการเคลือบชั้นรองพื้นนิกเกิลด้วยไฟฟ้า - รัญชน์ สงวนหมู่ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The galvanizing process whereby steel is electrodeposited with nickel and hot-dipped in a molten zinc bath at 450℃ is investigated as a potential route to mitigate the zinc-coating overgrowth problem and to improve the corrosion properties of the galvanized steels. The influences of processing parameters, including electrodeposited current waveforms, and the electroplating and galvanizing durations on the evolutions of microstructure and phase structures, the corresponding corrosion behaviors, and the adhesion properties of the galvanized low-carbon steels are explored and analyzed. Galvanized coatings prepared with the electrodeposition of nickel interlayer can be produced with uniform, void-free structure using a pulse-current waveform upon nickel deposition. A typical microstructure of this type of galvanized steels consists of two apparent zinc-nickel intermediate layers and a nickel layer that survives the galvanization. The uniformity of these layers can be ensured by providing a nickel pre-coating of suitable thickness in relation to the hot dip duration. The bending test demonstrates that such coating exhibits superior adhesion as compared to the coating of conventional type. The results from the salt spray tests demonstrate that galvanized coating with nickel precoating exhibits at least 2 times more enhanced corrosion resistance than the conventionally-galvanized steel, even though the thickness of the coating is 3 times smaller. The polarization potential study suggests that such improved corrosion performance is attributed to a low corrosion rate and a high corrosion potential of the Zn-Ni intermediate layers thus formed.